2021
DOI: 10.3389/fmicb.2021.675002
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing for Whole-Genome Characterization of Weissella cibaria UTNGt21O Strain Originated From Wild Solanum quitoense Lam. Fruits: An Atlas of Metabolites With Biotechnological Significance

Abstract: The whole genome of Weissella cibaria strain UTNGt21O isolated from wild fruits of Solanum quitoense (naranjilla) shrub was sequenced and annotated. The similarity proportions based on the genus level, as a result of the best hits for the entire contig, were 54.84% with Weissella, 6.45% with Leuconostoc, 3.23% with Lactococcus, and 35.48% no match. The closest genome was W. cibaria SP7 (GCF_004521965.1) with 86.21% average nucleotide identity (ANI) and 3.2% alignment coverage. The genome contains 1,867 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 75 publications
2
9
0
Order By: Relevance
“…We found 27 matches of putative virulence factor genes in the NH9449 genome, including tufA (elongation factor Tu), lisR (two-component response regulator), hasC (DP-glucose pyrophosphorylase) and SMU_322c (glucose-1-phosphate uridylyltransferase). These genes were previously reported in W. hellenica 0916-4-2 ( Panthee et al, 2019 ), and W. cibaria UTNGt21O ( Tenea and Hurtado, 2021 ). W. confusa FS54 encodes 133 virulence-associated genes, which is the highest number in this genus.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…We found 27 matches of putative virulence factor genes in the NH9449 genome, including tufA (elongation factor Tu), lisR (two-component response regulator), hasC (DP-glucose pyrophosphorylase) and SMU_322c (glucose-1-phosphate uridylyltransferase). These genes were previously reported in W. hellenica 0916-4-2 ( Panthee et al, 2019 ), and W. cibaria UTNGt21O ( Tenea and Hurtado, 2021 ). W. confusa FS54 encodes 133 virulence-associated genes, which is the highest number in this genus.…”
Section: Resultssupporting
confidence: 78%
“…For instance, W. cibaria can produce bacteriocins such as weissellicin 110, which has strong activity against Gram-positive bacteria ( Srionnual et al, 2007 ; Wu et al, 2015 ). Some W. cibaria strains were reported to encode and harbor several genes with useful biotechnological properties ( Carlosama Adriana et al, 2021 ; Tenea and Hurtado, 2021 ). They also play an important role in heterofermentative metabolism and CO 2 production from carbohydrate metabolism, which makes them suitable for use in fermentation processes ( Ricciardi et al, 2009 ; Kang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…With due caution, this may represent an exploitable feature if probiotics and antibiotics are coadministered to prevent gastrointestinal disorders due to the antibiotic treatment ( 59 ). We should underline that antibiotic resistance studies on Weissella and Periweissella are limited ( 16 , 61 ), and to date, no reference cutoff values are established to determine their antibiotic resistance. Here, we assessed the MIC values of the six Weissella and Periweissella type strains analyzed, evaluating antibiotic concentrations even 10-fold higher than the ones reported by the FEEDAP panel in the guidance on the assessment of bacterial susceptibility to antimicrobials of human and veterinary importance ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the COGs were classified into 26 functional categories except for Nohit against the COG database and of the 2556 protein-coding genes, 2259 genes (88.39%) were assigned to COGs categories. The W. cibaria UTNGt21O strain (1635 genes) reported by Tenea and Hurtado [39] was less than the W. cibaria JW15 strain. We found that the essential genes from the functional subcategories with the COG codes G (Carbohydrate transport and metabolism, 7.75%), J (Translation, ribosomal structure, and biogenesis, 7.67%), K (Transcription, 5.95%), L (Replication, recombination and repair, 4.38%), H (Coenzyme transport and metabolism, 3.44%), and I (Lipid transport and metabolism, 3.4%).…”
Section: Genomic Features Of Jw15 Strainmentioning
confidence: 77%